Global Dynamics of an HTLV-1 Model with Cell-to-Cell Infection and Mitosis. (12th August 2014) - Li, Sumei; Zhou, Yicang
Abstract : A mathematical model of human T-cell lymphotropic virus type 1 in vivo with cell-to-cell infection and mitosis is formulated and studied. The basic reproductive numberR 0 is derived. It is proved that the dynamics of the model can be determined completely by the magnitude ofR 0 . The infection-free equilibrium is globally asymptotically stable (unstable) ifR 0 < 1 ( R 0 > 1 ) . There exists a chronic infection equilibrium and it is globally asymptotically stable ifR 0 > 1 .